Single-molecule diffusion measurements for material characterization in one-dimensional nanostructured polymer films - Tran-Ba, Khanh-Hoa (Kansas State University, 2015)
This dissertation describes single-molecule tracking (SMT) measurements for the quantitative characterization of one-dimensional (1D) nanostructures in 200 nm-thick surfactant-templated mesoporous silica (STMS) and cylinder-forming polystyrene-poly(ethylene oxide) diblock copolymer (CF-PS-b-PEO) films with a μm-scale thickness. SMT is advantageous for the characterization of nanomaterials over conventional methods because it permits the simultaneous and quantitative assessment of the nanoscale and microscale morphologies, and mass-transport properties of the materials with a high nanometer-scale resolution under ambient conditions. It offers a unique means for the assessment and evaluation of the μm-scale nanostructure alignment in polymer films induced by vertical spin-coating (for STMS films), directional solution flow and solvent-vapor penetration (SVP) methods (both for CF-PS-b-PEO films), highly crucial for many potential technological applications using the materials. Through this work, we have identified suitable sample preparation conditions (e.g. solvent, temperature or solution flow rate) for obtaining highly-ordered mesoporous and microdomain structures over a long-range (> 5 μm). For the quantitative assessment of the 1D SMT data, orthogonal regression analysis was employed, providing assessment of the in-plane orientation and size of individual nanostructures with nanometer-scale precision. The analysis of the 1D trajectory data allowed the radius (ca. 11 nm) of cylindrical PEO microdomains to be estimated, yielding results consistent with the AFM results (ca. 14 nm). The distribution of the trajectory angles offered the estimation of the average orientation and order of the nanostructures in domains/grains for a μm-wide region of the polymer films, revealing the higher efficiency of SVP in the nanostructure alignment as compared to the spin coating and solution flow approaches. Systematic SMT measurements across the film depth and along lateral mm-scale distances afforded valuable insights into the shear- and solvent-evaporation-based alignment mechanisms induced by solution flow and SVP/spin coating approaches, respectively. Fluorescence recovery after photobleaching (FRAP) measurements in a SVP-aligned CF-PS-b-PEO film permitted the longer-range mass-transport properties to be probed, reflecting the effective continuity of the aligned cylindrical nanostructures over > 100 μm in length. In this dissertation, FRAP and more importantly SMT methods have provided a unique and useful means for the in-depth characterization of morphology and mass-transport characteristics in thin polymer films under ambient conditions, in confined spaces, and with a nanometer-scale resolution.
Keywords: Single-molecule tracking; Molecular diffusion; Material characterization; Fluorescence microscopy; Block copolymers; Quantitative data analysis